Analisis Pendapatan dan Nilai Tambah Industri Pengolahan Minyak Daun Cengkeh di Kabupaten Garut - Erawan, Wahid; Awaliyah, Fitri; Rusyana, Andi; Febrianti, Tintin (Universitas Galuh, 2026)
Garut Regency is one of the clove-producing areas in West Java with a fairly large area and high production. The development of clove crops is not only focused on increasing the production of traditional commodities, but has shifted towards diversifying processed products such as essential oils that have economic value. This study aims to determine the costs, revenues, and income, as well as the added value of the clove leaf oil processing industry in Garut Regency. The study was conducted using a quantitative descriptive method with the object of study being the clove leaf oil processing business in Panyindangan Village, Cisompet District, Garut Regency. The results show that the production costs incurred by the company for the clove leaf oil processing business per year (96 production periods) amounted to IDR 135,711,200 with revenues of IDR 328,320,000, and the company's profit amounted to IDR 192,548,800. The added value from the clove leaf oil processing business per production process obtained a total output of 19 kg of clove leaf oil from 480 kg of clove leaf raw material input, with the production providing an added value of IDR 4,688 with a high added value ratio of 65.112%.